Mosque institution and building: evaluating sustainable space, function, program, and activities - Asif, Nayeem; Utaberta, Nangkula; Ismail, Sumarni; Yan, Xin; Zhou, Yijiao (Springer Science and Business Media Deutschland Gmbh, 2023)
It was the norm for Muslim armies during the early period that whenever a new territory was conquered, the first establishment would be a mosque. That mosque served simultaneously as the military base, administrative office, and place for congregational prayers. However, in present time, the function of the mosque institution becomes more diversified and flexible. This paper aims to study the historical precedence of a mosque’s function as well as the current perception of the programs of a mosque. The paper adopts qualitative method through reviewing existing literature and analyze the data by descriptive analysis. Recommendations are made based on the findings which show that diversification of mosque’s functions is highly needed in present time as the Muslim community is facing rapid sociocultural changes. Moreover, inclusiveness of mosque institutions is significant to ensure participation from all strata of the community. Further research on these aspects can be done to study specific mosques in selected contexts.